Type 2 diabetes mellitus – conventional therapies and future perspectives in innovative treatment - Barbara Gieroba; Adrianna Kryska; Anna Sroka-Bartnicka (Biochemistry and Biophysics Reports)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by insulin resistance and dysfunction of the pancreatic beta cells, which leads to elevated blood glucose levels. Conventional therapies, including metformin, sulfonylureas, and insulin, have long served as the cornerstone of treatment. However, they often face limitations, such as adverse effects, reduced efficacy over time, and difficulties in achieving optimal glycemic control. This has sparked considerable interest in developing novel and experimental therapeutic strategies to enhance treatment outcomes. Recent advances in diabetes management feature dual incretin receptor agonists, like tirzepatide, which combine GLP-1 and GIP receptor agonism, resulting in increased insulin secretion, decreased glucagon release, and significant weight loss. Additionally, dual SGLT1/2 inhibitors, such as sotagliflozin, show promise for more significant blood glucose reduction and improved weight loss by targeting glucose regulation in both the gut and kidneys. Other promising methods include glucagon receptor antagonists, GPR119 agonists, and FGF21 analogs, which strive to enhance insulin sensitivity and improve glucose metabolism through innovative pathways. Gene editing technologies, including CRISPR-Cas9 and AMPK activators, are also being investigated to tackle the underlying pathophysiology of T2DM more effectively. While these experimental therapies show promise, their long-term safety and efficacy remain under research. This article reviews the conventional therapies currently in use. It investigates future perspectives on innovative treatments for T2DM, emphasizing the potential of these new therapies to transform diabetes care and enhance patient outcomes.